Redefining Turkey's Regional Economic Disparities Through Social Participation - Tuba Cekic (European Regional Science Association (ERSA), 2011)
Social capital is a common concept for both describing and understanding economical, political and social wellbeing of community. Although it has been defined by economists and sociologists; social capital concept is also highlighted in regional development strategies. Accordingly, assessing the role of social capital in regional development and the impact of social capital to economic growth by means of empirical and theoretical studies has been an important issue in the literature. The relation between social capital and regional economic development in Turkey, as a developing country, has been put forth as the main theme of this paper. The paper aims to provide an overview of the concept of social capital for regional development and discuss social capital in terms of social participation depending on the work of Robert Putnam. Although interregional disparities in Turkey have been studied by many academicians, revealing their relationship with participation is rather new. Searching for this relationship, indicators of social participation is converted to social capital index and regression analysis have been used to explore the relation between social capital and regional economic development. During the construction of indicies, principal component analysis and factor analysis is used to determine the weights of each indicator. Thus, this paper evaluates the social participation in NUTS II level regions in order to foreseen regional disparities in the context of economic development. At this point it has been asserted that social capital in regions both explains and is a result of regional economic development.
Keywords: 330